2012
DOI: 10.1055/s-0032-1323727
|View full text |Cite
|
Sign up to set email alerts
|

Activated Glucose-6-phosphate Dehydrogenase is Associated with Insulin Resistance by Upregulating Pentose and Pentosidine in Diet-induced Obesity of Rats

Abstract: Recent studies have shown that glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme for the pentose phosphate pathway, was involved in insulin resistance via reduced nicotinamide adenine dinucleotide phosphate, while the roles of pentose were not examined. In the present study, the association of G6PD, pentose, and pentosidine with insulin resistance was investigated in diet-induced obesity of rats. Male Wistar rats were fed a high-fat diet for 6 weeks to generate obesity-prone (OP, n=14) and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…Stimulation of the PPP pathway is associated with increased insulin resistance, increased NADPH production, and thus, increased production of free fatty acids [31]. Hence, our metabolomics findings may indicate increased glucose availability and utilization through glycolysis and the pentose phosphate pathway, owing to decreased insulin sensitivity in the males receiving resveratrol.…”
Section: Discussionmentioning
confidence: 93%
“…Stimulation of the PPP pathway is associated with increased insulin resistance, increased NADPH production, and thus, increased production of free fatty acids [31]. Hence, our metabolomics findings may indicate increased glucose availability and utilization through glycolysis and the pentose phosphate pathway, owing to decreased insulin sensitivity in the males receiving resveratrol.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, we did not observe this phenomenon in response to hu-nNOSÎŒ, despite the fact that hu-nNOSÎŒ and 6-AN produced similar results with regards to suppression of G6PDH and increases in insulin-independent glucose uptake. In individuals with T2D, infusion of a NO donor increases basal rates of leg glucose uptake [39]. Studies in isolated muscle strips have shown that this increased glucose uptake occurs through an insulin-independent signaling mechanism(s) [40].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Plasma protein AGEs, such as MG-H1 and 3DG-H, may be increased by dicarbonyl stress; 13 CML and glucosepane may be increased by elevated FL residue precursor and/or decreased FL metabolism; [16][17][18] and pentosidine residue content may be increased by elevated pentosephosphate pathway activity providing increased level of the pentose precursor. 19 AGE residue content of plasma protein is also influenced by decreased residence time of albumin in the vascular compartment by albuminuria, 20 increased transcapillary escape rateinfluenced by hypertension and atherosclerosis; 21 and also by decreased albumin synthesis and catabolism. 22 These confounders suggest AGE residue content of plasma protein has a complex relationship with clinical outcomes in CKD.…”
Section: Dicarbonyl Stressmentioning
confidence: 99%